INFLUENCE OF NORMOBARIC HYPOXIA ON THE PARAMETERS OF MENTAL WORKABILITY OF ATHLETES IN CYCLIC SPORTS - Tambovtseva R.V.; Sechin D.I.; Voytenko Yu.L.; Pletneva E.V. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to study the effect of normobaric hypoxia on the parameters of mental performance of highly qualified athletes of cyclic sports. Methods and structure of the study. The study was conducted in the laboratory of physiology of muscle activity and recovery of the Research Institute of Sports and Sports Medicine RUS "GTSOLIFK". Psychophysiological tests were used on the basis of the hardware-software complex "Sports psychophysiologist" and the method of hypoxic tests using the hypoxicator "Everest-1, mod.07m". Results and conclusions. It has been shown that a 30-minute exposure to normobaric hypoxia (10% O2) has a selective effect on individual components of mental performance, in particular on the sensorimotor and motor components associated with a decrease in the time spent on various reactions. According to the parameter of the tapping test, the performance of athletes decreases while maintaining the maximum rate of hand movements. The effectiveness of the normobaric hypoxia method characterizes it as an effective ergogenic remedy.